Brief Analysis of the Application of Abstract Language in Animation Special Effects Production - Piao, Tianqi; Wang, Ting (Transactions on Economics, Business and Management Research, 2024)
This article mainly elaborates on the research and exploration of geometric abstract elements in design works, traces their development and expressive characteristics, and further studies the practical development and significance of geometric abstract elements in design. It analyzes the influence of the use and expressive power of geometric elements in animation works.